Thermo-responsive smart windows for year-round energy savings - Li, Dan (Nanyang Technological University, 2022)
In the developed countries, 40% of total energy is consumed on buildings. The heating, ventilation, and air-conditioning (HVAC) systems of buildings spend up to 50% of the total building energy usage, to maintain a comfortable indoor temperature. It is urgent to develop energy-efficient buildings with reduced HVAC energy consumption and windows are considered as the least energy-efficient elements in buildings. Smart windows have received much attention because they can controllably modulate indoor temperature and thermal comfort by regulating the transmittance of near infrared ray (NIR) in smart ways. NIR with wavelengths from 780 nm to 2500 nm, contributes 44% of the whole solar energy (wavelengths range from 250 nm to 2500 nm) received by earth but cannot be detected by human eyes. Therefore, smart windows, which can block NIR in summer and allow NIR transmittance in winter, are excellent solutions for year-round energy savings. To date, the energy-saving smart windows mainly rely on mechano-, photo-, electro-, and thermos-responsive technologies. Among them, thermo-responsive smart windows are supposed to be highly promising candidates because of their low cost, easy fabrication, and passive response. In this thesis, two thermo-responsive smart windows for year-round energy savings have been investigated. Firstly, a new category of thermo-responsive smart window, named a butterfly-wing-like smart window (BSW), is developed based on deformable surface morphology created from shape memory polymer by imitating the dynamic behavior mechanism of butterfly wings. The BSW can be custom designed according to the sunlight incident angles of actual applications. Both high solar modulation (ΔTsol) of 32.6% and luminous transmission (Tlum) of 64.5% are achieved by a change in the projection area of the reflectance coating, resulting from the temperature-dependent surface morphology transition and the season-dependent incident angles variation. Further, a photothermal smart window with high mid-infrared (MIR, 2.5 μm to 25 μm) reflectance (PHMR) is developed, which can minimize radiative heat exchange between indoors and outside ambient surroundings, and have tunable reflectance in NIR region with solar transmittance modulation. This kind of thermo-responsive smart windows with high mid-infrared reflectance (RMIR) and controllable near-infrared reflectance (RNIR) have rarely been studied so far. The PHMR smart window provides a solution to year-round building energy savings by using cross-aligned silver nanowires (AgNWs) as the high RMIR film and a photothermal bimorph actuator to regulate RNIR. The PHMR smart window is highly reflective for MIR light (RMIR is high to 0.86 in winter and 0.97 in summer) to minimize radiative heat exchange between rooms and outside ambient surroundings and has tunable reflectance in NIR region with a high ΔTsol of 31.1%. The building energy-saving consumption simulations indicate that the BSW and PHMR smart windows are more energy efficient than the commercial low-E glass. These smart windows are expected to be used in energy efficient buildings to reduce building energy consumption.